Pendidikan Resolusi Konflik Berbasis al-Qurâan - Pasir, Supriyanto (Nadwa, 2013)
Conflict is a fact of human history due to the inherent incompatibility between the two powers. Among the instruments to resolve conflict is education through an integrated curriculum on conflict resolution. Conflict resolution is defined as a process which utilizes spectrum communication skills and analytical and creat-ive thinking to prevent, manage and resolve conflicts peacefully. Study of conflict resolution education is based on the Qurâanic verse. By using the method of the-matic analysis found at least twelve conflict resolution activities and the values of the Koran can be used as a conflict resolution education, namely: restraint and forgiveness, communicate wisely, do good and respect, mutual understand-ing, fraternity, open network, called for peace, back to the book of Allah, avoid prejudice, not degrading, vying for the better, to understand the meaning of ji-had.